Australia: a land of missed opportunities?. (2nd May 2017) - Greasley, David; McLaughlin, Eoin; Hanley, Nick; Oxley, Les
Abstract: Comprehensive Investment (CI) may provide an indicator of future changes in a country's per capita consumption. The authors explore the utility of the CI indicator for Australia by constructing CI data since 1861 and by estimating their relationship with changes in future consumption over periods of 50 years ahead. The CI measures include changes in natural, produced and human capital, and make allowance for exogenous technological progress. The results are used to consider how Australia's natural capital exploitation influenced the consumption of future generations. Further, the authors gauge if low CI relative to other leading OECD countries resulted in lower consumption levels in Australia over time than feasible, had it saved more.